A Gestão da Noite Urbana Carioca: entre discursos sobre ordem urbana e práticas socioeconômicas / Urban Night Policies in Rio de Janeiro: between discourses of urban order and socio-economic practices - Marcos Paulo Ferreira de Góis (Sociedade & Natureza)
This article deals with some concerns about the Rio de Janeiro’s urban nightlife in the last thirty years. In that way, we discuss the idea of urban night and nighttime-economy through urban plans, projects and policies. Preliminary conclusions points out that planners and social scientists are overthinking about urban centers when they are looking for nightlife activities. So we propose a decentered view about urban night. It is especially true when we argue about the appropriation of public spaces at night, which has been put aside in urban planning initiatives.